Forlano, L., & Glabau, D. (2024). Cyborg. The MIT Press Essential Knowledge Series. - Khobra, Ujjwal; Gaur, Rashmi (Journal of Posthumanism, 2024)
Laura Forlano and Danya Glabau’s Cyborg (2024), part of the MIT Press Essential Knowledge Series, situates complex debates surrounding contemporary cyborg studies for nonspecialist readers. By providing a detailed analysis of the challenges faced by the term ‘cyborg’ since its inception, Cyborg presents ‘cyborg-thinking’ as a way forward in confronting our collective technologized present(s). In the Introduction, the cyborg figure emerges as a sociocultural phenomenon, transgressing oppositions such as nature/artificiality, man/woman, and mind/body to understand disability, labor, human/nonhuman entanglements, and the future of inequalities with interconnected crises. In mapping the cybernetic, popular, and feminist discourses that have employed cyborg-thinking as a cartographic tool, Cyborg introduces “critical cyborg literacy” as a distinct approach to critically and creatively analyze the relationship between technology, society, and culture (4).